A PERCEPÇÃO DA LOGÍSTICA REVERSA SOB A ÓTICA DAS INDÚSTRIAS MOVELEIRAS EM ARAPONGAS, PARANÁ - VAEZA, RAFAEL FRANCO (2016)
The objective of this work was to verify the perception of reverse logistics from the optics of the furniture sector companies in the city of Arapongas - PR. Thus, the theoretical referential, the following topics were discussed: environmental management, sustainability, solid waste management, reverse logistics, legislative aspects among others focused on the environment and the furniture sector. In this competitive scenarios, where companies seek a differential, studies aim to asses which companies know about practice of reverse logistics, and which adopt environmentally correct actions in their productions processes are of utmost importance in the current context. The methods used in the search were exploratory and descriptive. The methodological approach adopted was an applied quantitative research. To collect data, was used a structured questionnaire with 13 closed questions for the consolidation of research. The study included thirty furniture companies in the city of Arapongas. After application of the instrument, the data were organized in spreadsheets and were not performed statistical inference or elaborate causality analysis. Firstly, the participating companies were characterized then were made the analysis and interpretation of data correlating them with the theoretical framework and the research objectives. The results identify that subjects respondents know only the concept of reverse logistics. It was found that all participating companies adopt environmentally appropriate actions in its processes and services demonstrating commitment to the environment, and 90% of them are in conformity with the environmental licensing by the IAP. In general, the processes the reverse logistics are present in an incipient way in the industries of the furniture sector surveyed, as only 6.67% said that there is a reverse logistics process deployed. Thus, it can be concluded that the furniture companies are aware of the concept of reverse logistics, but do not know the essence of a complete reverse logistics system, a fact that hinders the implementation of a logistics plan, which is considered an important tool for the preservation of environmental conditions.